Shear behaviour of prestressed precast SFRC girders. (1st July 2017) - Soetens, T.; Matthys, S.; Hertelé, S.; De Waele, W.
Highlights: This paper reports the results of 23 shear tests on prestressed SFRC girders. A digital image correlation (DIC) technique has been used. Addition of steel fibres leads to a more ductile shear failure. Abstract: The replacement of traditional shear reinforcement by the use of steel fibre reinforced concrete has been of special interest for precast concrete companies. In this way, they can increase production efficiency by eliminating the labour-intensive placing of traditional stirrups. Furthermore, the use of steel fibres will shorten the production process significantly. Although the feasibility of this technique has been proven in the past by both laboratory testing and real-life applications [3–8], its application cannot be considered as a daily practice. To get more insight into the shear behaviour of steel fibre reinforced concrete (SFRC) full-scale girders, an experimental programme has been performed on precast SFRC girders with a span of 20 m and a height of 1 m and with a fibre dosage ranging between 20 and 60 kg/m 3 . Thereby the development of shear cracks is investigated in more detail by means of a digital image correlation technique (DIC). The obtained test results reveal that for the girders with higher fibre dosages the shear load can be increased with 78% before reaching a crack width of 2.5 mm. However, considering the ultimate shear failure load of prestressed SFRC girders, the beneficial effect of steel fibres has been found to be limited for higher dosages.